2008
DOI: 10.1063/1.2837809
|View full text |Cite
|
Sign up to set email alerts
|

On the pressure-induced loss of crystallinity in orthophosphates of zinc and calcium

Abstract: A recently suggested mechanism for the stress memory of various metal phosphates is investigated experimentally. Based on first-principles simulations [N. J. Mosey et al., Science 307, 1612 (2005)], it had been argued that atoms with flexible coordination, such as zinc or heavy-metal cations, act as network-forming agents, undergoing irreversible pressure-induced changes in bonding that lead to increased connectivity between phosphate anions. In the present study, orthophosphates of zinc and calcium were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
6
24
0
Order By: Relevance
“…Present results clearly show that decomposition is dominant at high pressure. However, the simple zinc phosphate may cross link at high pressures as suggested in a recent experiment [14]. The thermal decomposition of ZDDP upon heating under pressure is in agreement with the results obtained from thermal treatment of ZDDP at ambient pressure.…”
Section: High-pressure High-temperature Effectsupporting
confidence: 84%
See 2 more Smart Citations
“…Present results clearly show that decomposition is dominant at high pressure. However, the simple zinc phosphate may cross link at high pressures as suggested in a recent experiment [14]. The thermal decomposition of ZDDP upon heating under pressure is in agreement with the results obtained from thermal treatment of ZDDP at ambient pressure.…”
Section: High-pressure High-temperature Effectsupporting
confidence: 84%
“…Under the current experimental P-T conditions, there is no substantial spectroscopic evidence to confirm the formation of a network glass structure as the result of cross-linkage via the phosphate groups. The results reported here show that the cross-linkage of phosphate groups in decomposed ZDDP may not be induced by pressure alone as suggested from the computer simulation [6], even though it was indeed observed in the model zinc phosphate system [14]. Therefore, the proposed molecular Fig.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This is to be expected as isolated PO 4 groups have already been shown to be stable in the pressure range investigated here. 2,22 Verification of the transition pressures suggested by the IR transmission spectroscopy can be done with the help of the XRD analysis.…”
Section: B Ir Spectroscopy During Compressionmentioning
confidence: 99%
“…It was also argued that the reversible coordination change at the cation site could explain the extraordinary stiffening ͑smart behavior͒ observed in the earlier nanoindentation experiments. 13 Subsequent high pressure experiments 12,22 provided evidence for a reversible pressure-induced cation coordination increase. They also indicated that strong stiffening occurs even without coordination change at the cation site.…”
Section: Introductionmentioning
confidence: 99%